2005
DOI: 10.1111/j.0022-202x.2005.23604.x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Point Haplotype Scores Telomeric to Human Leukocyte Antigen-C Give a High Susceptibility Major Histocompatability Complex Haplotype for Psoriasis in a Caucasian Population

Abstract: Psoriasis is a chronic inflammatory skin disease that affects 0.1%-5% depending on the population. PSORS1 is the major susceptibility locus, accounting for approximately 33%-50% of the genetic component of psoriasis among Caucasians. PSORS1 is located within the major histocompatibility complex (MHC) locus on 6p21.3. Its position has been refined to hundreds of kilobase and the region located at approximately 100-200 kb telomeric to human leukocyte antigen (HLA)-C is a very strong candidate. To determine the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
8
1
2
Order By: Relevance
“…The minimal candidate region of PSORS1 mapped by our study overlaps the regions mapped in an American Caucasian population [14] and a Jewish population [11], but is different from the ones mapped by other studies in Caucasian, Japanese and Sardinian psoriatic populations [9],[10],[12] (Fig 2). This difference could be due to the existence of different risk haplotypes in other populations.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The minimal candidate region of PSORS1 mapped by our study overlaps the regions mapped in an American Caucasian population [14] and a Jewish population [11], but is different from the ones mapped by other studies in Caucasian, Japanese and Sardinian psoriatic populations [9],[10],[12] (Fig 2). This difference could be due to the existence of different risk haplotypes in other populations.…”
Section: Discussioncontrasting
confidence: 83%
“…A 150-kb region telometic to HLA-C was also shown to be associated with psoriasis in a Jewish population [11]. More recently, Lench et al [12] performed a SNP-based association analysis and found strong association to a 46-kb interval telomeric to HLA-C in both Caucasian and Japanese populations. Helm et al [13] also performed a comprehensive case/control and family-based association study using SNPs and located the PSORS1 to a haplotype block harboring HLA-C and distinct from CDSN and HCR .…”
Section: Introductionmentioning
confidence: 98%
“…cgi), and MHC studies [9,11,18]. Comparing the prevalence of inherited diseases in Han Chinese and Caucasian populations, atherosclerosis related to AIF1 and psoriasis related to C6orf18 are more prevalent in Caucasians [26,27]; allopurinolinduced severe cutaneous adverse reaction related to BAT3 [18] and hepatitis B virus related to HLA-DRA are more prevalent in Han Chinese [28,29]. Furthermore, we also investigated genomic regions highly linked to the 101 SNPs and found that some are related to the etiology of diseases such as nasopharyngeal carcinoma, which is highly prevalent in Asian populations.…”
Section: Resultsmentioning
confidence: 99%
“…However, the exact location of the PSORS1 gene had been controversial, due to the extended and complicated linkage disequilibrium (LD) pattern of the region [5]. Early studies had indicated the existence of two major PSORS1 locations suggested by various fine mapping studies, one a region ∼150 kb telomeric to HLA-C [6],[7],[8],[9], harboring HCG27 , POU5F1 , TCF19 , CCHCR1 and CDSN , and the other HLA-C itself or very close [10],[11]. Recently, a combined sequencing and haplotype mapping study found that within the 298 kb homologous region between the two proposed risk haplotypes, only HLA-C encoded variants unique to these haplotypes at the level of translated protein, which at the same time conferred increased risk of psoriasis, strongly suggesting that HLA-C is the Ps susceptibility gene, and excluded the telomeric region [12].…”
Section: Introductionmentioning
confidence: 99%